Independent Chinese documentary : alternative visions, alternative publics - Edwards, Dan (Lecturer in film studies) (Edinburgh studies in East Asian film., 2015)
Analyses how independent documentaries are forging a new public sphere in today's China. Since the turn of the twenty-first century there has been an explosion in Chinese independent documentary filmmaking. But how are we to understand this vibrant burst of activity? Are these films brave expressions of dissidence, or do they point to a more complex attempt to expand the terms of public discourse in the People's Republic? This timely study is based on detailed interviews with Chinese documentary makers rarely available in English, and insights gained by the author while working as a journalist in Beijing. It considers the relationship between independent documentaries and China's official film and television sectors, exploring the ways in which independent films probe, question and challenge the dominant ideas and narratives circulating in the state-sanctioned public sphere. Detailed analyses of key contemporary documentaries reveal a sustained attempt to forge an alternative public sphere where the views and experiences of petitioners, AIDS sufferers, dispossessed farmers and the victims of Mao's repression can be publicly aired for a small, but steadily growing, public. Key Features: A detailed account of one of the world's most active, vibrant and challenging contemporary documentary sectors Draws extensively on first-hand interviews with filmmakers Offers in-depth, critical analyses of China's most challenging contemporary independent documentaries Discusses China's state-sanctioned film and television sectors to cast new light on how the official public sphere is shaped and guided by the state